Evaluasi Desain Antarmuka Portal Akademik Menggunakan Metode Heuristic Evaluation - Murdiaty Murdiaty; Angela Angela; Chatrine Sylvia (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2019)
Evaluation of interface design is part of human and computer interaction (HCI-Human Computer Interaction). The focus of this study is to conduct heuristic evaluations on the interface design of an academic portal to determine the extent to which the academic portal meets the concept of usability. Academic portal is a website accessed by academics through a web browser. This portal can be accessed by students, lecturers, academic supervisors, Final Project supervisors, and other academics such as: Academic Administration Section (BAA), Study Programs, Libraries, Student Affairs, and Public Administration and Personnel Section (BAUK). This study uses heuristic evaluation as an approach in evaluating a human-machine system (man-machine system) in relation to academic portal ease of use (usability) and also severity ratings in addition to heuristic checklist.  This study involved several evaluators who would conduct an assessment by filling in the heuristic checklist. The expected results with the evaluator's heuristic evaluation method found usability problems related to the general interface. These results are expected to be used by Mikroskil's academic portal system developers to make improvements to the academic portal currently in use